1997
DOI: 10.1161/01.res.80.1.45
|View full text |Cite
|
Sign up to set email alerts
|

p22phox mRNA Expression and NADPH Oxidase Activity Are Increased in Aortas From Hypertensive Rats

Abstract: Recent studies suggest that superoxide production by the NADPH/NADH oxidase may be involved in smooth muscle cell growth and the pathogenesis of hypertension. We previously showed that angiotensin II (Ang II) activates a p22phoxbased NADPH/NADH oxidase in cultured rat vascular smooth muscle cells and in animals made hypertensive by infusion of Ang II. To investigate the mechanism responsible for this increased oxidase activity, we examined p22phox mRNA expression in rats made hypertensive by implanting an osmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
332
3
12

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 490 publications
(367 citation statements)
references
References 22 publications
20
332
3
12
Order By: Relevance
“…The p22 PHOX functions as an integral subunit of the final electron transporter from NADPH to heme to molecular oxygen in generating superoxide anion (39). In this study, we found increased expression of p47 PHOX and p22 PHOX subunits of NADPH oxidase in the H group, thus indicating that this increase could be contributing to the activation of this enzyme complex, favoring the generation of ROS.…”
Section: Discussionsupporting
confidence: 48%
“…The p22 PHOX functions as an integral subunit of the final electron transporter from NADPH to heme to molecular oxygen in generating superoxide anion (39). In this study, we found increased expression of p47 PHOX and p22 PHOX subunits of NADPH oxidase in the H group, thus indicating that this increase could be contributing to the activation of this enzyme complex, favoring the generation of ROS.…”
Section: Discussionsupporting
confidence: 48%
“…Thus p22 phox is essential for the activation process of NAD(P)H oxidase. Meanwhile, several other laboratories confirmed the induction of the enzyme in diabetes and also in hypertension (Fukui et al, 1997;Griendling et al, 2000;Hink …”
Section: Induction Of Nad(p)h Oxidase By Hyperglycemiamentioning
confidence: 93%
“…134,135 OXIDATIVE STRESS AND HUMAN HYPERTENSION Almost all experimental models of hypertension show some form of oxidative excess including genetic forms (spontaneously hypertensive rats, stroke-prone spontaneously hypertensive rats), surgically induced (2K1C, aortic banding), endocrine-induced (Ang II, aldosterone, deoxycorticosterone acetate) and diet-induced hypertension (salt, fat). [21][22][23][136][137][138] Sources of ROS in experimental models include Noxes (Nox1, Nox2 and Nox4), xanthine oxidase, uncoupled nitric oxide synthase and mitochondrial oxidases. Mice deficient in ROSgenerating enzymes have lower blood pressure compared with wild-type counterparts, and Ang II infusion fails to induce hypertension in these mice.…”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%